Bryan Faussett : antiquary extraordinary - Wright, David, (Archaeological lives., 2015)
A biography of Bryan Faussett, F.S.A., (1720-1776), pioneering Kent genealogist, archaeologist and antiquary who, at his death, had amassed the world's greatest collection of Anglo-Saxon jewellery and antiquities. The material was famously rejected by the British Museum, saved for the nation by a Liverpudlian philanthropist, and now resides in the Liverpool World Museum.